Doctoral Programs Are in Anticipation of Change: Postgraduates and Their Scientific Supervisors’ Readiness - L. F. Krasinskaya; A. S. Klimova (Высшее образование в России, 2020)
Nowadays a postgraduate school reform is expected. It aims at enhancing the scientific preparation of postgraduate students and increasing the number of dissertations. It is planned that the educational process will be carried out in accordance with federal state requirements, and a dissertation will be presented as the final qualification work. Also, the educational accreditation of doctoral programs is going to be cancel. The article discusses the question how far universities are ready for these innovations, and presents the results of a survey aimed at studying the attitude of postgraduate students and their supervisors to the educational process in postgraduate school. The empirical data obtained indicate that the existing model of scientific and pedagogical personnel training is more focused on the educational activities rather than research, there is a mismatch between content of training courses and cognitive needs of students, and there are no necessary material and technical conditions for conducting experimental work. The expected increase in hours for research activities can lead to a reduction in the disciplines that ensure the formation of pedagogical competencies in postgraduate students. The authors believe that pedagogical education for postgraduate students of industrial universities, including technical ones, is necessary, since teachers of special disciplines are not massively trained anywhere. The solution of the question of the optimal ratio of scientific and educational training is possible through the introduction of individual educational paths, which are built taking into account the orientation of postgraduate students towards teaching or research activities.